Plastics recycling : (Distributed in the U.S.A. and Canada by Oxford University Press, 1992)
Widespread environmental concerns coupled with dwindling waste-management options have led to a growing demand for recycling programs in countless communities across the United States. This book describes today's plastics recycling technology, offering a wealth of information in one convenient considerable detail. Topics addressed include the chemistry, engineering, and economics involved; specialized equipment; collecting and sorting procedures; and new research and development activities. Patents and publications are referenced throughout. The book is uniquely organized according to resin types for easy access. This is an indispensable resource for plastics and materials engineers, technicians, entrepreneurs, and city-planning personnel who are either involved in on-going recycling operations or who need the facts for setting up such a service.